Hard Red Winter Wheat Variety—KS Bill Snyder - Guorong Zhang (Kansas Agricultural Experiment Station Research Reports, 2024)
KS Bill Snyder, a hard red winter wheat variety, was developed by the wheat breeding program at the Agricultural Research Center-Hays, Kansas State University and released by the Kansas Agricultural Experiment Station in 2023. KS Bill Snyder was selected from a single cross of KS11HW15/KS060476-M-6 using a modified bulk breeding method. KS Bill Snyder is an F4-derived line and has been tested in yield trials from 2018 to 2023 in Kansas before its release. It has performed well in both dryland and irrigated yield trials in western Kansas and surrounding regions. KS Bill Snyder has a medium maturity and medium-short stature. It has good grain shattering tolerance, and very good straw strength and winter hardiness. KS Bill Snyder also has a good disease-resistant package including resistance to stripe rust and soilborne mosaic virus; moderate resistance to wheat streak mosaic virus, leaf rust, and powdery mildew; and intermediate resistance to stem rust, Triticum mosaic virus, and barley yellow dwarf virus. Its test weight, milling qualities, and baking qualities are all above average.
Keywords: hard red winter wheat; variety; yield; disease; quality